Quality management for web services the requirements of interconnected business. - Weiser, Jay (SOA webservices journal.)
Web services provide organizations with a flexible, standards-based mechanisms for deploying business logic and functionality to distributed consumers. Consumers, whether internal or external, can access necessary components such as account information, credit card validation and much more. When business functionality is distributed, however, quality management becomes imperative. Mission-critical functions, sensitive data transmission and fee-based services must work quickly and accurately for all users all the time. To ensure that this high level of quality is met, organizations must employ strong test processes to ensure that necessary Web services are developed and deployed to meet the highest standards.